Acetyltransferase GCN5 regulates autophagy and lysosome biogenesis by targeting TFEB. (21st November 2019) - Wang, Yusha; Huang, Yewei; Liu, Jiaqi; Zhang, Jinna; Xu, Mingming; You, Zhiyuan; Peng, Chao; Gong, Zhefeng; Liu, Wei
Abstract: Accumulating evidence highlights the role of histone acetyltransferase GCN5 in the regulation of cell metabolism in metazoans. Here, we report that GCN5 is a negative regulator of autophagy, a lysosome‐dependent catabolic mechanism. In animal cells and Drosophila, GCN5 inhibits the biogenesis of autophagosomes and lysosomes by targeting TFEB, the master transcription factor for autophagy‐ and lysosome‐related gene expression. We show that GCN5 is a specific TFEB acetyltransferase, and acetylation by GCN5 results in the decrease in TFEB transcriptional activity. Induction of autophagy inactivates GCN5, accompanied by reduced TFEB acetylation and increased lysosome formation. We further demonstrate that acetylation at K274 and K279 disrupts the dimerization of TFEB and the binding of TFEB to its target gene promoters. In a Tau‐based neurodegenerative Drosophila model, deletion of dGcn5 improves the clearance of Tau protein aggregates and ameliorates the neurodegenerative phenotypes. Together, our results reveal GCN5 as a novel conserved TFEB regulator, and the regulatory mechanisms may be involved in autophagy‐ and lysosome‐related physiological and pathological processes. Synopsis: GCN5‐mediated TFEB acetylation inhibits autophagy and lysosome biogenesis by disrupting the dimerization and DNA binding of TFEB. GCN5 negatively regulates autophagy and lysosome biogenesis. TFEB is a direct acetylation substrate of GCN5. Acetylation disrupts TFEB dimerization and DNA binding. Interfering with GCN5‐mediated acetylation of TFEB/dMitf reduces Tau aggregation and neurotoxicity in Drosophila . Abstract : GCN5‐mediated TFEB acetylation inhibits autophagy and lysosome biogenesis by disrupting the dimerization and DNA binding of TFEB.